Study on Open Defecation Free in Kelurahan Kelayan Tengah Banjarmasin City - Mazaya, Gusti Ihda; Noya, Hendrawati; Soedjono, Eddy Setiady (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2015)
Endeavors toward Universal Target of 2019 dealing with water and sanitation are not merely the responsibility of central and local government, since community is both the subject and object of the target achievement. One of the main obstacles in accomplishing this target is the practice of open defection in a number of areas in Indonesia. This study was aimed to assess Open Defecation Free (ODF) in the environment applying the off-site sanitation system. The study was conducted in Kelayan Tengah village, Banjarmasin, consisting of 232 households in which 117 of them are still practicing open defecation (OD). The study was commenced by reviewing relevant literatures, conducting field survey (questionnaire and interview), and analyzing the data by using Analytical Hierarchy Process (AHP). The analysis included the assessment of technical aspect, social cultural aspect, and institution aspect. Questionnaire was fulfilled by 75 respondents, while AHP involved 5 respondents. Action Plans of open defecation free in Kelayan Tengah village encompassed the establishment of Waste Water Treatment Plan (WWTP) in Elementary school of Kelayan Tengah village to design 117 house connections out of 232 house, the organization of community and public discussion with theme of proper sanitation, and the improvement of coordination of sanitation working group. Action Plans to achieve Open Defecation Free in Kelayan Tengah village, Banjarmasin encompassed the possibility of using Kelayan Tengah 2 Elementary School as the site to establish waste water treatment plant (WWTP) to provide the toilet access for 117 houses which cannot afford the appropriate ones; the effort to disseminate the importance of toilet and to organize public discussion with theme of proper sanitation; the improvement of coordination among sanitation working groups to maintain open defecation free and agencies that play a role in this issue, as well the promotion to conduct fund collaboration between public and government for the purpose of ODT.